Stability of second-order recurrences modulo pr - Lawrence Somer; Walter Carlip (International Journal of Mathematics and Mathematical Sciences)
The concept of sequence stability generalizes the idea of uniform distribution. A sequence is p-stable if the set of residue frequencies of the sequence reduced modulo pr is eventually constant as a function of r. The authors identify and characterize the stability of second-order recurrences modulo odd primes.